The Fluid Frontier: Blacks and the Detroit River Region. A Focus on Henry Bibb - Cooper, Afua (Canadian Review of American Studies, 2000)
The French named the body of water that connects the upper Great Lakes to the lower ones “the detroit,” meaning “strait.” As a main artery of the Great Lakes and the river system of that region, the Detroit River has come to exert a crucial influence on the land and people on both its banks and adjacent areas. From earliest times, this river served as a natural border between the various First Nations groups that first settled the region, including the Fox, the Ojibway, the Pottowatami, and the Ottawa, and the Europeans who came later.1 The first Europeans, the French, who settled and traded in the area under the lead of Lamothe Cadillac, founded the town of Detroit in 1701. This was on the side that would eventually become “American.” Soon, another settlement was established on the south bank of the river, the side that would become “Canadian.” Under the French regime, both sides were considered units of the same polity, the colony of New France.2